Goals for, insecurity in, and self-perceptions of peer status: short term longitudinal associations with relational aggression and prosocial behaviors in emerging adults - Findley-Van Nostrand, Danielle; Campbell, Benjamin (Frontiers in Developmental Psychology, 2024)
Research on relational aggression in adolescents suggests it is in part driven by the desire to attain and maintain enhanced status among peers, and recent work also suggests certain forms of prosocial behaviors are similarly status-motivated. However, these associations are not well understood in young adults. In this short-term longitudinal study across 8 months (N = 215), we examined whether relational aggression and two forms of prosocial behaviors (altruistic and public) are related to social goals for popularity and preference, social status insecurity, and self-perceptions of status (in terms of dominance and prestige) concurrently and over time in emerging adults (age 18–25). Social goals for popularity predicted increases in relational aggression and public prosociality and were negatively related to and predicted decreases in altruistic prosociality. Preference goals were concurrently negatively related to relational aggression and to public prosociality and were positively related to and predicted increases in altruistic prosociality over time. Social status insecurity moderated links between self-perceptions of status and aggressive/prosocial behaviors, which were largely non-significant without considering status insecurity. Finally, tests of indirect effects suggest that aggression and prosociality mediate associations between popularity goals and self-perceptions of dominance. Findings suggest that strategic use of aggression and prosociality may not be developmentally limited to adolescence.